2015
DOI: 10.7314/apjcp.2015.16.2.707
|View full text |Cite
|
Sign up to set email alerts
|

A Logistic Model Including Risk Factors for Lymph Node Metastasis Can Improve the Accuracy of Magnetic Resonance Imaging Diagnosis of Rectal Cancer

Abstract: Comprehensive Cancer Network., 2014). Establishment of an indication for neoadjuvant therapy requires evaluation of nodal staging and T stage and mesorectal fascia (MRF) involvement. If the symptoms are underestimated due to inaccurate nodal staging, the patient

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…At present, the diagnostic ability of T staging, mesorectal fascia (MRF) invasion and extramural vascular invasion (EMVI) are widely recognized clinically and can be used as an important basis for the diagnosis and treatment of rectal cancer. 1 However, preoperative assessment of N staging that relies on MR criteria is not optimistic, 2 despite lymph node metastasis (LNM) being an important risk factor for disease-free survival and local recurrence. 3 The European Society for Medical Oncology (ESMO) guidelines 4 recommend that low-risk patients with T3N0 do not need preoperative neoadjuvant chemoradiotherapy (nCRT) and only need treatment with total mesorectal excision (TME).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the diagnostic ability of T staging, mesorectal fascia (MRF) invasion and extramural vascular invasion (EMVI) are widely recognized clinically and can be used as an important basis for the diagnosis and treatment of rectal cancer. 1 However, preoperative assessment of N staging that relies on MR criteria is not optimistic, 2 despite lymph node metastasis (LNM) being an important risk factor for disease-free survival and local recurrence. 3 The European Society for Medical Oncology (ESMO) guidelines 4 recommend that low-risk patients with T3N0 do not need preoperative neoadjuvant chemoradiotherapy (nCRT) and only need treatment with total mesorectal excision (TME).…”
Section: Introductionmentioning
confidence: 99%
“…A model including clinical stage N, age, stage T, and body mass index proposed by Ogawa et al had a sensitivity, specificity, and AUC of predicting LN metastasis in rectal cancer patients of 0.723, 0.774, and 0.785, respectively 29 . The corresponding values in our study were 0.854, 0.847, and 0.903, respectively, suggesting that the diagnostic effectiveness of the current predictive model was higher than that of their model.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated intensification of systemic therapy with neoadjuvant combination chemotherapy before standard treatment is feasible in poor-risk potentially operable rectal cancer with acceptable safety and promising long-term outcomes, for it can eradicate micrometastasis by implementation of a full systemic dose [ 22 , 23 ]. In term of metastatic LNs assessment, as the presence of microscopic metastases or inflammatory swelling of LNs, the preoperative metastatic LNs assessment remains a challenging problem for radiologists [ 19 ]. In our study, a short axis diameter of greater than 5mm, irregular borders or mixed signal intensity was used as the diagnostic criteria for metastatic LNs.…”
Section: Discussionmentioning
confidence: 99%
“…The MRI has been considered as the imaging modality of choice for the preoperative staging of rectal cancer; however, LNs staging is still challenging for MRI [ 17 , 18 ]. The diagnostic accuracy of MRI for assessing the LN metastasis varies from 57% to 85% [ 19 ]. On the other hand, the serum carcinoembryonic antigen (CEA) is known to be a widely available tumor marker for preoperative evaluation and postoperative detection of distant metastasis in patients with rectal cancer [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%